Nigeria-india Economic, Political And Sociocultural Relations: Critical Reflections For Continuous Mutual Co-operation - Balarabe Kura, Sulaiman (Penerbit Universiti Sains Malaysia (USM Press), 2009)
The establishment of the Diplomatic House in Nigeria in 1958 (two years prior to Nigerian independence) by India laid the foundation for what was to become solid, warm and concrete bilateral relations between India and Nigeria. The subsequent diplomatic and commercial visits between officials of the two countries crystallised and concretised their cooperative ties regarding political, economic and socio-cultural issues. This paper examines the politico-diplomatic, socio-cultural and economic relations between India and Nigeria. Using a historical approach, the paper argues that although in economic terms the balance of trade is in favour of Nigeria due to increasing importation of Nigeria's crude oil into India, Indian investment activities in Nigeria have exemplified what might be termed an unequal relationship in which India has an edge over Nigeria. Nevertheless, in view of the magnitude of the cordial relations between the two countries, their development potentials and some socio-political and cultural commonalities, they stand a very good chance of further solidifying and enriching their interactions with regard to several important issues, such as the development of democratic institutions and the redefinition of economic relations between the two states. This, the paper argues, would not only strengthen their political and economic relations, but also bring mutual benefits.